2022
DOI: 10.1101/2022.02.23.22271397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When mistrust in the government and scientists reinforce social inequalities in vaccination against Covid-19

Abstract: Objective To assess whether mistrust in the government and scientists reinforces social and racial inequalities in vaccination practises Design A follow-up of a random population-based cohort survey. Setting In July 2021, in France. Participants 80,971 participants aged 18 years and more. Main outcome measures Adjusted odds ratios of Covid-19 vaccination status (received at least one dose/ intends to get vaccinated/ does not know whether to get vaccinated/refuses vaccination) were assessed using multinomial … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…These accessibility issues may also explain the association we find between lower vaccination rates and living in a district with a high proportion of immigrants, which may for instance reveal language barriers. These associations of lower vaccination rates with more poverty and with higher proportions of immigrants in the district of residence are compatible with the results of a survey conducted in July 2021 in France (Bajos et al 2022) on close to 81000 participants, which indicated that unvaccinated respondents were more likely to have lower income and more likely to belong to racialised minorities than vaccinated respondents…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These accessibility issues may also explain the association we find between lower vaccination rates and living in a district with a high proportion of immigrants, which may for instance reveal language barriers. These associations of lower vaccination rates with more poverty and with higher proportions of immigrants in the district of residence are compatible with the results of a survey conducted in July 2021 in France (Bajos et al 2022) on close to 81000 participants, which indicated that unvaccinated respondents were more likely to have lower income and more likely to belong to racialised minorities than vaccinated respondents…”
Section: Discussionsupporting
confidence: 87%
“…K. Ward et al 2022; Lindholt et al 2021). A survey conducted in July 2021 in France confirmed that trust in the government and trust in scientists were associated to higher odds to be vaccinated (Bajos et al 2022). Votes for Mr Asselineau – which represented a minority of cast votes in 2017 in France (less than 1% overall) – can be interpreted as mistrust in the government (or more generally, against the establishment): This candidate for instance proposed that France exits the European Union, leave the Euro zone and reinstall the Franc currency; he was a proponent of hydroxychloroquin and ivermectin during the Covid-19 pandemic, and publicly expressed doubts about the safety of available Covid-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation